HAND, FOOT AND MOUTH DISEASE: A REVIEW - Lisa Lailatannur (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Abstract Background: Hand, foot and mouth disease or HFMD is a common childhood infectious disease mainly caused by coxsackievirus A16 (CVA 16) and enterovirus 71 (EV71). This HFMD disease can spread throughout the world and also cause outbreaks. Occurrence of this disease is mostly reported in the summer and fall. However, in Indonesia itself, HFMD is still not getting enough attention due to its self-limiting nature, so there is not enough epidemiological data.Objective: This research was conducted to find out the description of hand, foot, and mouth disease or HFMD.Methods: Conducting a literature review of previous journal articles related to hand, foot, and mouth disease or HFMD.Results: HFMD caused by coxsackievirus A16 or CVA16 and enterovirus 71 or EV71 which are self-limiting. Contact with saliva, fluids, and feces of HFMD patients can trigger transmission. Meanwhile, vaccines and antivirals have not been found that can be a way to treat and prevent EV71.Conclusion: One solution that is considered effective for preventing HFMD is to always practice clean living. Keywords: Hand, foot and mouth disease; HFMD; eEV71; CVA16; A16